Inhibition of harringtonine-induced apoptosis by tetradecanoylphorbol acetate in human leukemia HL-60 cells - Meng Fan-Hong; He Qi-Yang; Zhang Hong-Qing; Xue Shao-Bai (Acta Pharmacologica Sinica; Vol 18, No 5 (September 1997): Acta Pharmacologica Sinica, 2016)
AIM: To study the changes of the apoptosis induced by camptothecin (Cam) or harringtonine (Har) in human leukemia HL-60 cells after the cells were preincubated with tetradecanoylphorbol acetate (TA). METHODS: Chromatin condensation observation, flow cytometry, DNA agarose gel electrophoresis, and Dot blot hybridization. RESULTS: After the HL-60 cells were preincubated with TA 200 nmol.L-1 for 6 h, the apoptosis induced by Har 0.1 mg.L-1 for 3 h was drastically inhibited, and the apoptosis by Cam 0.2 mg.L-1 for 3 h was partly inhibited. On the other hand, the expression level of c-myc gene in HL-60 cells decreased apparently after the preincubation of TA. CONCLUSION: TA preincubation inhibited the apoptosis induced by Har obviously or by Cam partly in human leukemia HL-60 cells, and the expression of c-myc gene decreased drastically in the preincubated cells, which might result in the inhibition of apoptosis.